Genome-wide characterization of the PP2C gene family in peanut (Arachis hypogaea L.) and the identification of candidate genes involved in salinity-stress response - Wu, Zhanwei; Luo, Lu; Wan, Yongshan; Liu, Fengzhen (Frontiers in Plant Science, 2023)
Plant protein phosphatase 2C (PP2C) play important roles in response to salt stress by influencing metabolic processes, hormone levels, growth factors, etc. Members of the PP2C family have been identified in many plant species. However, they are rarely reported in peanut. In this study, 178 PP2C genes were identified in peanut, which were unevenly distributed across the 20 chromosomes, with segmental duplication in 78 gene pairs. AhPP2Cs could be divided into 10 clades (A-J) by phylogenetic analysis. AhPP2Cs had experienced segmental duplications and strong purifying selection pressure. 22 miRNAs from 18 different families were identified, targeting 57 AhPP2C genes. Gene structures and motifs analysis exhibited PP2Cs in subclades AⅠ and AⅡ had high structural and functional similarities. Phosphorylation sites of AhPP2C45/59/134/150/35/121 were predicted in motifs 2 and 4, which located within the catalytic site at the C-terminus. We discovered multiple MYB binding factors and ABA response elements in the promoter regions of the six genes (AhPP2C45/59/134/150/35/121) by cis-elements analysis. GO and KEGG enrichment analysis confirmed AhPP2C-A genes in protein binding, signal transduction, protein modification process response to abiotic stimulus through environmental information processing. Based on RNA-Seq data of 22 peanut tissues, clade A AhPP2Cs showed a varying degree of tissue specificity, of which, AhPP2C35 and AhPP2C121 specifically expressed in seeds, while AhPP2C45/59/134/150 expressed in leaves and roots. qRT-PCR indicated that AhPP2C45 and AhPP2C134 displayed significantly up-regulated expression in response to salt stress. These results indicated that AhPP2C45 and AhPP2C134 could be candidate PP2Cs conferring salt tolerance. These results provide further insights into the peanut PP2C gene family and indicate PP2Cs potentially involved in the response to salt stress, which can now be further investigated in peanut breeding efforts to obtain cultivars with improved salt tolerance.